TEKNOLOGI PENGELOLAAN BENIH SUMBER KEDELAI DI PROVINSI JAMBI - Yardha Yardha; Atman Atman (Jurnal Sains Agro, 2022)
Soybean seed is one of the production inputs that contributes significantly to increasing productivity and yield quality. The availability of soybean seeds with high-yielding and high-quality varieties, both physical, physiological, genetic, and pathological qualities is absolutely necessary in an agricultural production system. This activity aims to produce and disseminate soybean-sourced seeds as well as increase the capability and capacity of breeder farmers in producing soybean-sourced seeds. The activity was carried out in Dusun Baru Village, VII Koto District, Tebo Regency and Simpang Village, Berbak District, East Tanjung Jabung Regency in January - December 2018. Using the Anjasmoro variety (SS seed class) covering an area of 38 hectares in the Harapan Mulya Farmer Group, Dusun Baru Village, VII Koto District, Tebo Regency, covering an area of 32 hectares with 25 cooperating farmers and an area of 6 hectares in Keltan Jati Mulya, Simpang Village, Berbak District, Tanjung Jabung Timur Regency with 3 cooperating farmers. The results of the captive breeding show: (1) Through the development and assistance of seed, harvest, post-harvest farmer groups and improvement of group administration, the supply of seeds from outside the area can be reduced or even eliminated; (2) The success of this seed breeding can help meet the needs of source seeds in Jambi Province. The guidance and assistance of breeder farmer groups that are carried out, especially the cultivation of seed technology, harvesting, post-harvest and group administration improvements are adopted by farmers. Capability and capacity of breeder farmers increased. Seen by the success of producing seeds and getting an award as the best breeder group of Jambi Province; and (3) Jambi Province is one of the national soybean production centers, but has not been able to be independent in providing quality and labeled seeds. From year to year they still bring in seeds from outside the region, especially from Java and Lampung. Financially, captive soybean farming is feasible with indicators R/C 1.63, TIP 977.91 kg/ha, and TIH IDR 9,779/kg. The profit of farming to produce seeds is higher IDR. 8.350.000/ha/planting season compared to the profit of consumption soybean farming.